Life after surgical resection of a meningioma: a prospective cross-sectional study evaluating health-related quality of life - Nassiri, Farshad; Jungk, Christine (Neuro-Oncology, 2019)
Background: Few studies have evaluated the health-related quality of life (HRQoL) of patients with meningiomas. Here, we report the largest prospective, longitudinal cross-sectional cohort study of HRQoL in meningiomas to date, in order to identify possible actionable determinants of global HRQoL. Methods: Adults who had undergone resection of a grade I intracranial meningioma and were in routine follow-up at a single large tertiary center underwent HRQoL assessment using the QLQ-C30 questionnaire administered opportunistically at follow-up visits. Averaged transformed QLQ-C30 scores at 12-month intervals were compared with scores from a normative reference population, with reference to known minimal clinically meaningful difference (CMD) in scores. To evaluate for possible determinants of changes in global HRQoL, global HRQoL scores were correlated (Spearman’s Rho) with subdomain and symptom scores and with interval time from surgical resection. Results: A total of 291 postoperative patients with histologically confirmed and surgically treated grade I meningiomas consented to participation and a total of 455 questionnaires were included for analysis. Patients with meningiomas reported reduced global HRQoL at nearly every 12-month interval with clinically and statistically significant impairments at 12, 48, 108, and 120 months postoperative compared with the normative population (P < 0.05). Meningioma patients at the 12-month interval also reported a reduction of each subdomain of HRQoL assessment (P < 0.05); however, a CMD was only seen in cognitive functioning. Physical, emotional, cognitive, and social subdomains, as well as fatigue and sleep/insomnia, were significantly associated with global HRQoL at the first 12-month interval. Overall, there was no significant correlation between time from surgery and global HRQoL or the subdomain functional or symptom sections of the QLQ-C30. Conclusions: Meningioma patients report considerable limitations in HRQoL for more than 120 months after surgery, particularly in cognitive, emotional, and social function, as well as suffering significant fatigue and sleep impairment compared with a normative reference population. The majority of these reported functional impairments and symptoms are strongly associated with global HRQoL and thus can be considered determinants of global HRQoL that if treated, have the potential to improve HRQoL for our meningioma patients. This hypothesis requires future study of targeted interventions to determine their efficacy.
Gesehen am 12.07.2019